Surface cooling caused by rare but intense near-inertial wave induced mixing in the tropical Atlantic - Rebecca Hummels (Nature Portfolio, 2020)
How the tropical mixed layer of the ocean reacts to near-inertial waves has rarely been observed directly. Here, the authors present new data that shows strongly elevated vertical diffusive heat flux in the presence of near-inertial waves, causing a cooling of the mixed layer that is particularly strong in summer.